2019
DOI: 10.14295/cs.v10i1.2440
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Losses in Watersheds in the Western-Center Meso-Region Rio-grandense

Abstract: Article AbstractThe permanent monitoring of sediment losses in small-paired watersheds is still incipient, especially in what concerns the search for information that combines variables that are part of an open and dynamic system. In this sense, this work investigated sediment losses in watersheds in the Western Meso-region Rio-grandense from 07/2010 to 12/2012. The auxiliary variables were composed of rainfall, surface and base flow and kinetic energy -in comparison to the morphometry of each microbasin and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The soil water repellency is an indicator used in the assessment of land degradation. It is defined as the inability to get wet or water to seep into the soil , it is an unstable phenomenon, it is more pronounced when the soil is drier, it can happen naturally or after forest fires (Robichaud et al, 2000) and it is generally indicated as the reduction of the amount of water infiltration in the soil (Telman et al, 2000;Krolow et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The soil water repellency is an indicator used in the assessment of land degradation. It is defined as the inability to get wet or water to seep into the soil , it is an unstable phenomenon, it is more pronounced when the soil is drier, it can happen naturally or after forest fires (Robichaud et al, 2000) and it is generally indicated as the reduction of the amount of water infiltration in the soil (Telman et al, 2000;Krolow et al, 2019).…”
Section: Introductionmentioning
confidence: 99%